Ecophysiology of Ocimum basilicum with thermopriming and its effect on Peronospora belbahrii - Romero-Bastidas, Mirella; Murillo-Amador, Bernardo; Hernández-Montiel, Luis Guillermo; Troyo-Dieguez, Enrique; Nieto-Garibay, Alejandra (Ecosistemas y Recursos Agropecuarios, 2022)
Downy mildew (Peronospora belbahrii) affects severely the development of Ocimum basilicum; its control is complicated due to the restricteduse of fungicides. The objective of this study was to subject basil var. Nufar seeds to thermopriming treatments at 40, 50 and 60°C in different exposure time intervals (30, 60 and 90 min) to assess the existing relationship betweendisease symptom emergence and relative humidity, environmental temperature and seed pre conditioning treatment effects on plant disease severity, incidenceand physiological response. The seeds weresowed in mesh house pots and when plants reached 15 cm, they were infected with P. belbahrii. Disease incidence was determined weekly; at 60 days after sowing, morphometric and physiological variables were determined showing significant differences between temperature, exposure time and interaction in the majority of the variables assessed. A decreasein disease incidence was observed in plants from seed thermopriming treated at 60°C for 60 min of exposure. This same treatment was found to show less stomatal opening and transpiration and greater substomatal concentration of CO2, which suggested a probable relationship P. belbahrii entering the leaf decreasing its incidence.
Keywords: Control, growth, mildew, temperature y vigor